Promoting Healing and Resilience in People with Cancer: A Nursing Perspective - Grossman, Mary.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This is the first Nursing book on cancer care designed around a conceptual model of whole person care. Key concepts are stress, healing, resilience and health. As a clinical model, nursing goals, desired outcomes, key concepts and proposed psychosocial interventions with patients and family caregivers, advance the practice of clinical nursing toward a more comprehensive understanding of the whole person with cancer and their loved ones. As a model for teaching nursing students about chronic illness, it provides a scientific basis for students to learn how to assess and care for the whole person and his loved one. As a model for clinical research in the field of cancer care, it serves as a predicate for the development, evaluation and interpretation of clinical interventions. The model is a dynamic framework that both informs and is informed by research findings. It is hoped that future research findings will reveal the optimal combination of interventions to provide comprehensive care across clinical contexts. With a patient-centred humanistic focus anchored by the quality of the nurse patient and family caregiver relationships, it is hoped that the nurse's technical, procedural and medical expertise may complement rather than define the nurse's approach to the whole patient and family. The book is structured to facilitate the reader's easy access to needed information. Each chapter examines a key concept of the model, and is organized around an introduction, learning objectives, definitions, and relevant research findings that serve as the scientific predicate for suggested interventions discussed in Part 4, Nursing approaches. Clinical and personal anecdotes, tables and figures illustrate the concepts under discussion. Nurse practitioners, clinic nurse specialists, nursing professors, graduate students, and nurse researchers may find this book a useful reference for conceptualizing whole person care, and for determining relevant interventions that promote healing, resilience and health. But it is also relevant for family doctors and fourth year students learning to care for the whole person with a chronic illness.
PART -- 1 Stress, healing and resilience in the whole person with cancer. 1 -- Introduction 2 -- Stress, healing and resilience conceptual model of nursing 3 -- Psychological stress PART 2;- Resilience 4 -- Introduction 5 -- Biological resilience 6 -- Psychological resilience PART 3 -- Poor resilience 7 -- Introduction 8 -- Poor resilience 9 -- Cancer PART 4 -- Fostering healing 10 -- Introduction 11- Nurse-patient (family caregiver) relationship 12 -- Promoting cognitive-behavioral adaptive coping 13 -- Enhancing meaning, purpose and acceptance 14 -- Strengthening supportive relationships 15.-Psychological healing and leveraging the placebo effect 16 -- Enhancing the relaxation response and mindful meditation 17 -- Use of touch, healing touch and massage PART 5 -- Clinical approaches 18 -- Introduction 19 -- Diagnosis 20 -- Treatment 21 -- Transition to Survivorship 22 -- End of life 23 -- Closing remarks: Is it feasible 24 -- Final comments.
Keywords: Nursing; Oncology; Family medicine; Clinical psychology; Nursing; Oncology; General Practice and Family Medicine; Clinical Psychology; Neoplasms -- nursing